New inorganic scintillators on the basis of LBO glass for neutron registration - Zadneprovski, B.I.; Eremin, N.V.; Paskhalov, A.A. (Functional Materials, 2005)
Undoped lithium borate glasses and those doped with Сu, Се, Sm, Eu, Тb, Тm, Yb have been synthesized; the optical and luminescence properties thereof have been determined as well as some scintillation characteristics at registration of neutrons (Eₙ ≤ 10 MeV) and of the ⁶⁰Со у radiation. The lithium borate glassy scintillators have been established in experiment to have a high sensitivity to neutrons and to be suitable to record selectively neutrons in mixed radiation fields. The results obtained evidence that such scintillators can be an alternative of promise to the known neutron detectors based on gases, liquids, plastics, and crystals.